KONTRIBUSI EKONOMI IBU RUMAH TANGGA BEKERJA SEBAGAI PEDAGANG TERHADAP KEHARMONISAN RUMAH TANGGA DI PASAR SIMPANG BARU PANAM - Syafira, Aulia; ", Nurhamlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This study aims to determine the characteristics and economic contribution of housewives working as traders and their relationship with household harmony. This research was conducted at Simpang Baru Market, Simpang Baru Village, Tampan District, Pekanbaru City which is supervised by the Pekanbaru City Trade and Industry Service with a total of 50 housewives who work as traders.This study uses a survey research method with a quantitative approach. This research generally aims to explain (explanatory) the conditions in the field. Based on the research results, the average income generated by housewives working as traders in Simpang Baru Market is Rp. 3,245.00 per month. The total household income averaged Rp. 7,115. 000 with the economic contribution given by housewives to work of 45.96% for the household economy. The relationship between economic contributions and household harmony was analyzed using the Spearman Rank correlation test, which shows the magnitude of the correlation is equal to0.123 then this value indicates a "low" relationship or there is no significant relationship between economic contributions and household harmony. Keywords : Contribution, Harmony